Healing our Planet and Society - History, Theories, Challenges, and Prospects - Baldev S Lamba (Fábos Conference on Landscape and Greenway Planning, 2025)
The Notion that nature is important to healing goes back at least to when temples to Asclepius, Greek god of healing, were built high on hilltops overlooking the sea. Aristotle believed walks in the open air clarified the mind. Darwin and Einstein walked in the gardens and grooves to help them think. We live in a world of duality or opposites. To develop a complete mind, study the art of science and the science of art and learning the fact that everything a connected to everything else. Taking two opposites and entangling them together in order to create a complete vision of the whole. Leonardo DaVinci The wisdom of ancient cultures is now being acknowledged and proved though scientific research, reinforcing the idea that connections with the natural world is fundamental to human happiness, heath, well-being, spirit and the very survival. In A Sand County Almanac, Aldo Leopold set forth his most enduring idea, the “land ethic,” a moral responsibility of humans to the natural world. At its core, the idea of a land ethic is simply caring: about people, about land, and about strengthening the relationships between them. E.O Wilson’s Biophilia Hypothesis suggests that humans possess an innate tendency and genetic disposition to seek connections with nature. The pervasiveness of spiritual reverence for animals and nature in cultures worldwide are evidence of biophilia. Environmental psychologist Dr. Roger Ulrich was the first to use medical research to demonstrated that gazing at a garden can speed healing from surgery, infections, and other ailments. The increasing populations, especially due to urban migration, since the 1950s along with our growing impacts of climate change is having a negative impact on the Earth systems with increased greenhouse gas, ocean acidification, deforestation and biodiversity deterioration, and poses unprecedented challenges for a symbiotic relationship between humans and nature. Building on the history and theories, this presentation will argue for understanding research-based importance of our genetic connections to nature, the challenges we are facing the some possible strategies for reconnecting humans and nature.